The Teaching of Drawing in the Era of Web 2.0 - Sílvia Simões (2010)
Our proposal attempts to clarify some issues that seem relevant when talking about the process of using information and communications technology (ICT) [1] applied to the teaching and learning drawing. On the text we'll look at the contribution of ICT to arts education and how it seems that the implementation of networked education can contribute to a dynamic and collaborative learning, and the possibility to promote the digital tool in the conceptualization and development of a Project.